A different leisure life: leisure experiences of snowbirds. Issue 4 (2nd October 2018) - Wood, Laura; Kulczycki, Cory
ABSTRACT: This study examined older adults' engagement in leisure while snowbirding in their second homes. Data were collected through observations and interviews with 24 participants in one gated community in Southern Florida, USA. Study participants described a more active leisure life in their second homes compared to their primary residences in Ontario, Canada. Four main factors contributed to this difference, including availability of leisure options, inclusivity and friendliness of others, shared interests and stage of life course and a temporary escape from family commitments. Thus, engaging in snowbirding served as an inadvertent negotiation strategy that removed constraints and, as a result of facilitators, lead to increased participation in leisure. Theoretically, this study adds to the body of literature identifying the role that constraints, negotiation strategies and leisure facilitators play in older adults' leisure engagement.